2022
DOI: 10.3346/jkms.2022.37.e22
|View full text |Cite
|
Sign up to set email alerts
|

Health and Mortality in Korean Healthcare Workers

Abstract: Background To evaluate the health status of healthcare workers (doctors and nurses) compared to those in the general population based on the National Health Insurance Service database and the cause of death data from Statistics Korea. Methods The subjects of this study were 104,484 doctors and 220,310 nurses working in healthcare facilities from 2002 to 2017, and who had undergone at least one general medical examination. Based on the subject definition, the subject dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Excess SIRs in the breast, mesothelial and soft tissue, and female genital organs were observed only in female HHCWs. This is consistent with the findings of a previous study that the highest causes of cancer-related mortality were bronchial and lung cancer in male HHCWs and breast cancer in female HHCWs [ 8 ]. One possible explanation for this phenomenon is the different job distributions between the sexes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Excess SIRs in the breast, mesothelial and soft tissue, and female genital organs were observed only in female HHCWs. This is consistent with the findings of a previous study that the highest causes of cancer-related mortality were bronchial and lung cancer in male HHCWs and breast cancer in female HHCWs [ 8 ]. One possible explanation for this phenomenon is the different job distributions between the sexes.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reported high cancer incidence among HCWs [ 5 , 6 , 7 ]; however, the results were inconsistent. Furthermore, a standardized cancer incidence among HHCWs in South Korea has not been reported, although cancer in HCWs has been consistently focused on and issued in the occupational safety and health area [ 8 , 9 , 10 ]. This study aimed to investigate the high incidence of cancer among HHCWs compared with total workers and public officials.…”
Section: Introductionmentioning
confidence: 99%
“…Beneficiaries who did not fit into the employee type category were referred to as local-type beneficiaries. Employment status was defined by the Occupational Regulations (INDTP_CD) codes in the qualification database of the NHIS [ 9 ]. If any occupational information was identified, the subject was classified as a “worker” and if not, a “non-worker”.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, analyzing the mortality rates due to the causes of death of healthcare practitioners, their values asso-ciated with malignant neoplasms were high enough. The prevalence of respiratory and gastrointestinal systems diseases was also higher than in general population (Shin et al 2022). Interviewing doctors in Finland revealed that, on average, they consider their working condi-tions to be good and better than those in representatives of other professional groups.…”
Section: Introductionmentioning
confidence: 93%